The Practice of Sheep Veterinary Medicine - Abbott, Kym (University of Adelaide Press, 2018)
This book is intended to be a reference text for veterinarians who provide clinical services to sheep producers. It is directed first and foremost at Australian sheep-raising systems, but the approaches described herein will have wide application in all countries where sheep are raised under extensive grazing conditions. Most of the important conditions of sheep in Australia are relatively straightforward to diagnose, but the establishment of effective and economically sound control strategies is often the most difficult part of health management, particularly for those who are less familiar with sheep production systems. With six initial chapters focusing on providing readers with a basic understanding of the business and science underpinning sheep production, this book focuses its remaining chapters on reproduction and disease conditions, ordered largely on a systems basis. The book provides details about the way disease processes develop and manifest in sheep flocks, with numerous references for those who wish to read further. Australian sheep production is a profitable and fulfilling agricultural pursuit for a large number of farm owners, and this book is intended to assist those who work in the industry to add to the profitability and efficiency of sheep production systems, the quality of sheep products and the welfare of the sheep in those systems.